Make a Match Learning Model with the Assistance of Wordwalls on Elementary School Science Learning Outcomes - Muhamad Aidil Nur Azani; Banun Havifah Cahyo Khosiyono; Akbar Al Masjid; Ana Fitrotun Nisa; Berliana Henu Cahyani (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Conventional teaching methods are often considered ineffective and have been associated with low student learning outcomes. This study aims to analyze the effect of student learning outcomes in the IPAS subject by implementing the cooperative learning model of the make a match type assisted by a word wall. The research employed a quasi-experimental design. The research subjects consisted of 52 students divided into an experimental class (26 students) and a control class (26 students). The subjects were selected using cluster random sampling. Data were collected through observation, interviews, and achievement tests. The research instruments included questionnaires and test items. Data analysis techniques involved statistical analysis using pretest and posttest t-tests. The results of the study indicate that the application of the make a match learning model assisted by a word wall had a significant effect on students’ learning outcomes. This finding is evidenced by the higher mean scores of the experimental class compared to those of the control class. It can be concluded that the make a match learning model assisted by a word wall results in a significant difference in students’ learning outcomes.